Regulamentação do uso medicinal da cannabis sativa e a problemática da jucialização do direito fundamental à saúde no Brasil - Silva, Thiago Jean Lima da (Universidade Federal Rural do Semi-Árido, 2017)
The National Agency for Sanitary Surveillance - ANVISA recently approved the registration of the first cannabis sativa drug in Brazil, in the face of recurrent changes to allow the importation of drugs that contain substances derived from the herb. Despite the dense body of anti-drug laws in Brazil, authorization for the use of drugs derived from cannabis sativa, characterizes the beginning of the entity's change of understanding about the administration of the substance for medicinal purposes. As a counterpart to this position, there was an increase in lawsuits, in parallel with the administrative process of authorization of entry of these medicines in the country, in the face of its administrative bureaucracy. In this sense, the present work aims to critically analyze the change of understanding of the autarchic entity, considering that before the resolution of the Collegiate Board No. 17/2015, the importation of cannabis-derived drugs was prohibited. From the methodological point of view, the bibliographic method was used as a research method, considering that the sources of information are secondary in nature, such as: books, articles, magazines. It is also a systematic research, since it intends to analyze the need for consistency of normative order of the Brazilian State of the use of medicines based on cannabis sativa.
Artigo Acadêmico
Keywords: Cannabis sativa; Judicialização da saúde; Agência Nacional de Vigilância Sanitária; Cannabis sativa; Judicialization of health; National Health Surveillance Agency; CIENCIAS SOCIAIS APLICADAS::DIREITO